Growth-Oriented Adjustment Programs : Proceedings of a Symposium held in Washington, D.C., February 25-27, 1987. (International Monetary Fund, 1987)
This volume presents the proceedings of a symposium that was orgainzed jointly by the IMF and the World Bank and held in Washington, D.C. The symposium was organized by Vittorio Corbo, Morris Goldstein, and Mohsin Khan. The papers review the design of, and the economic rationale behind, adjustment programs and examine the best means of helping developing countries achieve balance of payments stability with sustainable economic growth.